A Novel Endosurgical Prosthesis to Treat Thoracoabdominal Aortic Aneurysm in Complex Anatomy or Emergency Settings - Saitto, Guglielmo; Scafuri, Antonio; Kuci, Saimir; Ibrahimi, Alfred; Zeitani, Jacob (AORTA, 2020)
Background Despite improvements in operative techniques, open thoracoabdominal aortic aneurysm (TAAA) repair is complex and characterized by high mortality and morbidity rate. Less invasive techniques have been developed since 2005 for the treatment of TAAA. Unfortunately, many of these devices require custom fabrication, resulting in delay of many weeks until treatment can be delivered but crucial in critical emergency cases. We present a novel hybrid endovascular and surgical prosthesis, which was tested on five pigs, with the aim of reducing the barrier issues of endovascular therapy in such particular cases.Methods The principal characteristic of the proposed hybrid endovascular prosthesis is to combine a proximal and distal stented zones and, in between, a classical surgical blood tied Dacron prosthesis. The device was tested in five pigs where feasibility of implantation and acute postoperative outcomes were evaluated, including bleeding, bowel ischemia, renal function, and peripheral blood perfusion.Results In all cases, following laparotomy, the endoprosthesis was successfully implanted under fluoroscopy and the surgical prosthesis zone could be easily detected by the radio-opaque markers. No major bleeding or cardiac events occurred throughout preparation and implantation. One hour after prosthesis implantation and surgical anastomoses of all vessels were completed, normal urine output was registered, and no acidosis was detected.Conclusions This novel graft has shown ease of endoprosthesis and visceral vessels implantation without the need of thoracotomy or extracorporeal circulation and may be useful in an emergency setting or high risk and complex anatomy TAAA unsuitable for traditional endovascular aneurysm repair, or to avoid an excess waiting time for a “custom made” prosthesis. The great adaptability of this “hybrid” prosthesis in complex anatomy for the majority of TAAA could be important in high-risk patients and in some difficult situations, such as a high risk of imminent rupture.
Keywords: thoracoabdominal aortic aneurysm; endovascular approach; hybrid prosthesis